The Concept of Al-’Adl in Mu’tazilite Theology: An Analysis of Human Agency and Moral Accountability in the Modern Era - Ratna Sari Munthe; Nurliana Damanik (PT. Riset Press International, 2026)
Human problems in the modern era demand a re-examination of moral responsibility, particularly as human error is frequently detached from the individual and redirected toward systems, circumstances, technology, or fate. In this context, the concept of al-’adl (justice) in Mu’tazilite theology remains highly relevant, as it asserts that Divine justice is inseparable from human freedom and responsibility. This article aims to analyze the concept of al-’adl within Mu’tazilite theology and its implications for human agency and moral accountability in the modern era. Using a qualitative library research method with a theological-philosophical approach, this study demonstrates that al-’adl is not merely a core doctrine regarding God’s justice, but also a rational foundation for the position of humans as moral subjects. Mu’tazilite theology emphasizes that it is impossible for God to act unjustly, let alone burden humans beyond their capacity or punish them for actions not consciously chosen. Consequently, humans are understood as moral agents possessing reason, will, capability, and freedom of choice. From this agency arises moral accountability the human responsibility for every chosen action to be accounted for before Allah. This sutudy contributes to contemporary Islamic ethics by recontextualizing classical Mu’tazilite theology to address modern crises of accountability, offering a framework to analyze human agency within complex, systemic environments. Thus, the implications of al-’adl serve as a critique of fatalism, rejecting the use of destiny or system failures as excuses to evade moral responsibility. Nevertheless, a modern reading of al-’adl requires a deeper interpretation that considers the dynamic factors influencing human choices.